The Function of Informal Social Networks in the Context of Human Migration - Teshale, Getu Ambaye; Senthil kumar, A.P. (International Journal of Psychosocial Rehabilitation, 2020)
This article synthesizes studies that deal with the linkages between informal networks and migration. The concept of social network and its analysis has become increasingly popular in a wide range of issues and problems. The issue of migration taking place either voluntarily or forcefully has also become a growing problem. Nevertheless, systematically organized knowledge on the utility of informal networks for migrant people has been nonexistence. To this end, the systematic review was conducted to understand the current state of the art in the knowledge about the function of informal networks among migrant people. The study reveals that there are various ways by which informal networks provide supports and assistances for migrant people. The study also indicates that the function of social networks is easily identified across voluntary and forced migrants. The study also reveals that social networkbased research is relatively far more advanced in voluntary migration than in forced migration situations. The article is important as the first such review on the demonstration of social network analysis as a methodology in migration research which has not been well recognized in the study context. The study has implications for social work practice especially for advocacy work among migrants who are in need of support during the crisis.